Territorial Inequality in Internet Connectivity Among Mexican Households Between 2015 and 2021: A Spatial Statistics Approach - Sánchez-Alcalde, Luis Amado (2025)
This article analyzes the behavior of internet connectivity in Mexican households between 2015 and 2021. Using descriptive and spatial statistics, the data show that inequality in internet access decreased and that average dispersion also declined, although gaps and asymmetries persist among the 32 federal entities. States with low connectivity—mainly located in the south—form a cluster, while those with high connectivity group into another cluster in the north. Both clusters spread spatially and spill over into the connectivity of neighboring states. These asymmetries between a predominantly connected north and a structurally lagging south highlight the urgent need for differentiated public policies with a spatial focus, supported by technical inputs that acknowledge the influence of the socioeconomic dynamics specific to each entity.